2020
DOI: 10.3892/mmr.2020.11486
|View full text |Cite
|
Sign up to set email alerts
|

A novel identified circular RNA, circ_0000491, aggravates the extracellular matrix of diabetic nephropathy glomerular mesangial cells through suppressing miR‑101b by targeting TGFβRI

Abstract: circular rnas (circrnas) have crucial roles in various diseases; however, the mechanisms of action underlying circrnas in the occurrence and development of diabetic nephropathy (dn) remains largely unknown. The present study investigated the differentially expressed circrnas in the dn mice kidney cortex using circrna sequencing and elucidated the role of circrnas in mesangial cells. it was revealed that 40 circrnas were unconventionally expressed, including 18 upregulated circrnas and 22 downregulated circRNAs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 38 publications
1
20
0
Order By: Relevance
“…Since the abnormal development of MCs was correlated with the pathological changes of DN, MCs have been widely utilized for DN research in vitro [23,24]. In current work, the upregulation of circ_0000712 in the db/db DN mice and HG-triggered MCs was verified, in agreement with the previous study [14]. Also, our data showed the stability of circ_0000712, suggesting the underlying diagnostic and prognostic biomarker for DN.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Since the abnormal development of MCs was correlated with the pathological changes of DN, MCs have been widely utilized for DN research in vitro [23,24]. In current work, the upregulation of circ_0000712 in the db/db DN mice and HG-triggered MCs was verified, in agreement with the previous study [14]. Also, our data showed the stability of circ_0000712, suggesting the underlying diagnostic and prognostic biomarker for DN.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, Chen et al found that circLRP6 as a competing endogenous RNA (ceRNA) of miR-205 to boost HGtriggered MCs proliferation, oxidative stress, and inflammation in DN [13]. Of note, a prior study indicated that a novel circRNA, circ_0000712 was identified to be increased in kidney tissues and HG-inducted MCs [14]. To our knowledge, the precise role and underlying mechanism of circ_0000712 in DN remain largely unknown.…”
mentioning
confidence: 99%
“…CircRNA_010383 has been reported as a miR-135a sponge to increase the level of TRPC1 in regulating the high glucose (HG)-induced renal fibrosis in DN [ 11 ]. Circ_0000491 has exacerbated the accumulation of ECM in mesangial cells by inhibiting miR-101b to upregulate the TGFβRI expression [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, research on circular RNAs and their role in the health and disease of diabetic kidneys is gaining momentum as well. circRNA_15698, circLRP6, circACTR2, circHIPK3 and circ_0000491 are associated with renal inflammation and fibrosis whereas circRNA_010383 is reno-protective [ 135 , 136 , 137 , 138 , 139 , 140 ]. Therefore, better understanding of the role of these regulatory circular RNAs in the physiology of diverse kidney cell types is needed.…”
Section: Lncrna-mirna-based Treatment For Dkd Future Directions and Perspectivesmentioning
confidence: 99%